2011
DOI: 10.1111/j.1467-7652.2011.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis: a century of research, development and commercial applications

Abstract: SummaryBacillus thuringiensis (Bt) is a soil bacterium that forms spores during the stationary phase of its growth cycle. The spores contain crystals, predominantly comprising one or more Cry and ⁄ or Cyt proteins (also known as d-endotoxins) that have potent and specific insecticidal activity. Different strains of Bt produce different types of toxin, each of which affects a narrow taxonomic group of insects. Therefore, Bt toxins have been used as topical pesticides to protect crops, and more recently the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
433
0
19

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 679 publications
(457 citation statements)
references
References 70 publications
5
433
0
19
Order By: Relevance
“…Recent, research has classified B. thuringiensis as a bacterial pathogen of alternative nematode hosts (2)(3)(4), which may help to explain the complex ecology of B. thuringiensis that was previously thought to have a sole insect host (2,5,6). This finding further contextualizes already established interactions between B. thuringiensis and nematodes (1)(2)(3)(4)7), including free-living and parasitic species.…”
mentioning
confidence: 57%
“…Recent, research has classified B. thuringiensis as a bacterial pathogen of alternative nematode hosts (2)(3)(4), which may help to explain the complex ecology of B. thuringiensis that was previously thought to have a sole insect host (2,5,6). This finding further contextualizes already established interactions between B. thuringiensis and nematodes (1)(2)(3)(4)7), including free-living and parasitic species.…”
mentioning
confidence: 57%
“…To date, B. thuringiensis has been reported to produce over 760 kinds of ICPs that are classified into 72 Cry groups (723 kinds) and 3 Cyt groups (37 kinds) (http://www.lifesci.sussex.ac.uk/Home/ Neil Crickmore/Bt/; November, 2012), which endow it with an extensive spectrum of insecticidal activity (4). Moreover, many studies have confirmed that B. thuringiensis is one of the safest microbial products known (5). Therefore, it is widely used as a biopesticide for agricultural and public health applications.…”
mentioning
confidence: 99%
“…GM soybean has made rapid strides in recent decades, and its cultivation area has been increasing yearly. Currently, genetic modification has been successful in maize, tomato, rice and cotton plantations (Sanahuja et al, 2011;Tabashnik et al, 2011), mainly by inserting exogenous genes (transgene) that encode a protein that is toxic to specific pests.…”
Section: Biotechnological Development Of Agriculturementioning
confidence: 99%